ترقية نتيجة تعلم النحو باستخدام طريقة دورة الألعاب الجماعية في المدرسة المنزلية شعائر الله بيكاسي - Muhammad Kamal bin Abdul Hakim; Romdani Romdani; Dian Priandini (IAIN Salatiga, 2019)
The purpose of this research was to know the enhancement of learning results of Arabic grammar by using the Teams Games Tournament method in 10th grade at Home Schooling Sya'airullah Bekasi. The method used was the classroom action research with the study the student of Home Schooling Sya’airullah Bekasi 10th grade which amounted to 40 students as the sample. The research was conducted at Home Schooling of Sya’airullah Bekasi in March - April 2019. The classrom action research was conduct by using the Kemmis and Mc Taggart cycle model through four stages: planning, action, observation and reflection. The instruments used were learning results tests and observation sheets. Learning results tests were used to measure the success of students in understanding arabic grammar, while the observation sheet was used to measure teacher and student performance in learning. The result obtained by the students during the research was average 70.87 in the first cycle and 88.52 in the second one. Then, the enhancement from the first cycle to the second cycle was 17.65. Based on the results above, the researcher concluded that the Teams Games Tournament method can improve students' ability to understand the science arabic grammar and can improve the learning results of arabic grammar in 10th grade students at Home Schooling Sya'airullah Bekasi.